VD_FINDINFO Arrêt / 2024 / 1005 vom 25. November 2024 - VD Tribunal cantonal (2024)
AC, INDEMNITÉ EN CAS D'INSOLVABILITÉ, DOMMAGE, DILIGENCE, REJET DE LA DEMANDE | 51 LACI, 52 al. 1 LACI, 53 LACI, 55 al. 1 LACI